Pengaruh Reliability (Keandalan) dan Responsiveness (Daya Tanggap) Terhadap Kepuasan Pengguna Layanan Pengaduan Rakyat Online Dinas Komunikasi, Informatika dan Statistik Kota Denpasar - Sagung Dwiyanti Indraswari; I Gede Agus Wibawa (Public Inspiration : Jurnal Administrasi Publik, 2026)
The development of e-Government in Indonesia promotes the digitalization of public services to enhance transparency and public participation. One such initiative is PRO Denpasar, a digital complaint platform managed by the Communication, Informatics, and Statistics Office (Diskominfos) of Denpasar City. This service allows citizens to submit complaints online, which are then followed up by the relevant agencies. However, PRO Denpasar still faces challenges, such as uncertainty in complaint resolution and insufficient responsiveness, which can reduce public trust and decrease service effectiveness. This study aims to analyze the impact of reliability and responsiveness on user satisfaction with PRO Denpasar using a quantitative approach with multiple linear regression analysis. The respondents were citizens of Denpasar City who had used the service. Data was collected through questionnaires measuring users' perceptions of reliability, responsiveness, and satisfaction. The results indicate that both reliability and responsiveness have a positive and significant impact on user satisfaction. Reliability has a Standardized Coefficients Beta value of 0.279 (significance 0.000), while responsiveness is 0.304 (significance 0.000). Together, these two variables contribute 67.5% to user satisfaction, with responsiveness having a more dominant effect. To improve service effectiveness, complaint resolution must be accelerated by strengthening the monitoring system for OPD performance, automating complaint status updates, and developing a real-time tracking system. Regular evaluations are also necessary to ensure complaints are fully resolved. Through continuous improvements, PRO Denpasar is expected to become a more responsive, transparent, and citizen-oriented service.